3D radiative transfer simulations of Eta Carinae's inner colliding winds - I. Ionization structure of helium at apastron - Clementel, Nicola; Madura, T. I.; Kruip, C. J. H.; Paardekooper, Jan-Pieter; Gull, T. R. (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. The highly eccentric binary system Eta Carinae (η Car) shows numerous time-variable emission and absorption features. These observational signatures a